2016
DOI: 10.1299/jtst.2016jtst0049
|View full text |Cite
|
Sign up to set email alerts
|

Primary soot particle distributions in a combustion field of 4 kW pulverized coal jet burner measured by time resolved laser induced incandescence (TiRe-LII)

Abstract: To develop accurate models for the numerical simulation of coal combustion field, detailed experimental data using laser techniques, which can figure out the basic phenomena in a coal flame, are necessary. In particular, soot is one of the important intermediate substances in a coal flame. This paper is the first paper in the world reporting soot particle size distributions in a coal flame. The spatial distribution of the primary soot particle diameter were measured by the combination of the time-resolved lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
1
21
1
1
Order By: Relevance
“…For the RANS solution, one can use a presumed PDF for temperature pulsation to obtain the pulsation value of . Burn 51 et al investigated the effect of component scales in PDF on temperature self-correlation, yielding values between 0 and 2.5 for C TRI 1 . Using β-PDF, C TRI values suitable for furnace pulverized coal combustion can be obtained for component distribution coefficients at different locations.…”
Section: Resultsmentioning
confidence: 99%
“…For the RANS solution, one can use a presumed PDF for temperature pulsation to obtain the pulsation value of . Burn 51 et al investigated the effect of component scales in PDF on temperature self-correlation, yielding values between 0 and 2.5 for C TRI 1 . Using β-PDF, C TRI values suitable for furnace pulverized coal combustion can be obtained for component distribution coefficients at different locations.…”
Section: Resultsmentioning
confidence: 99%
“…One way to mitigate this problem is to use a very long focal length lens [8] or a combination of lenses [9,10]. Another possibility is to collimate the laser sheet both in the height and thickness directions instead of using a cylindrical lens to focus the laser sheet [11], but at the expense of a lower spatial resolution orthogonal to the beam sheet. Often however, there is an expectation that the effect of a varying laser sheet width leads to less uncertainty than other uncertainties in the LII measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Since volatile matter combustion is the first step in pulverized coal combustion and affects its subsequent phenomena. The investigation of the reaction kinetics of coal and optical measurement was conducted in previous studies (Ahn et al, 2016;Hashimoto et al, 2016;Lee et al, 2015). Ahn et al (Ahn et al, 2016) investigated reaction kinetics of the volatile matter from coal particle based on analyses with reduced chemical mechanism.…”
mentioning
confidence: 99%
“…They showed that hydrocarbons such as aromatics, methyl and ethyl groups play important role in the ignition and flame propagation processes. Hashimoto et al (Hashimoto et al, 2016) investigated soot particle size distributions in a coal flame with the time-resolved laser induced incandescence (TiRe-LII) method and the thermophoretic sampling (TS) method. They showed that soot volume fraction and the primary soot particle diameter increases with increasing the height above the burner in any radial distance from the ensemble-averaged TiRe-LII images.…”
mentioning
confidence: 99%